Sinner - Stiefvater, Maggie 1981- (New York Scholastic Press, 2014)
Cole St. Clair has come to California for one reason: to get back Isabel Culpeper
Isabel fled from Cole's damaged, drained life... and damaged and drained it even more. He doesn't just want her, he needs her. Isabel is trying to build herself a life in Los Angeles. She can play the game as well as all the other fakes, but what's the point? Cole and Isabel have the power to love each other and the power to tear each other apart. The only thing for certain is that they cannot let go
1
Keywords: Human-animal relationships -- Juvenile fiction; Metamorphosis -- Juvenile fiction; Paranormal fiction; Wolves -- Juvenile fiction; Human-animal relationships -- Fiction; Metamorphosis -- Fiction; Supernatural -- Fiction; Wolves -- Fiction; California -- Juvenile fiction; California -- Fiction